2018
DOI: 10.1007/s10021-018-0231-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soil Frost Versus Summer Drought as Drivers of Plant Biomass Responses to Reduced Precipitation: Results from a Globally Coordinated Field Experiment

Abstract: Reduced precipitation treatments often are used in field experiments to explore the effects of drought on plant productivity and species composition. However, in seasonally snow-covered regions reduced precipitation also reduces snow cover, which can increase soil frost depth, decrease minimum soil temperatures and increase soil freeze-thaw cycles. Therefore, in addition to the effects of reduced precipitation on plants via drought, freezing damage to overwintering plant tissues at or below the soil surface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
2
8
1
Order By: Relevance
“…Pant biomass decreased significantly in the two cultivars affected by drought stress, similar to the results of previous studies reported for other plant species [ 27 , 28 ]. This effect might be due to decreases in photosynthesis and chlorophyll content [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pant biomass decreased significantly in the two cultivars affected by drought stress, similar to the results of previous studies reported for other plant species [ 27 , 28 ]. This effect might be due to decreases in photosynthesis and chlorophyll content [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pant biomass decreased signi cantly in the two cultivars affected by drought stress, similar to the results of previous studies reported for other plants species [23,24]. The effect might be due to decreases in photosynthesis and chlorophyll content [25].…”
Section: Discussionsupporting
confidence: 89%
“…Following the networks’ protocols, nitrogen fertilization was applied in spring and year-round rain-out shelters set up in order to simulate conditions of nitrogen loading and a one in 100-year drought. First analysis within the International Drought Net showed that precipitation reduction (i.e., drought) significantly reduced minimum soil water content and above-ground biomass (mainly in forbs) at the experimental site in Freiburg (Henry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%